Micro-hydropower potential assessment and generation volatility due to seasonal climate - Khan M.R.B.; Jidin R.; Pasupuleti J.; Shaaya S.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper proposes hydropower potential sites for a resort island located in the South China Sea. Furthermore, the effects of seasonal climate to hydropower generation are also discussed. The resort island selected is Tioman, as it represents the typical energy requirements of many resort islands in the South China Sea. The island relies mainly on diesel-fuel for electricity generation. However, diesel is subjected to high and volatile market prices, high operation and maintenance costs, and poses environmental risks. Therefore, to mitigate diesel fuel dependency, reconnaissance studies were conducted through topographic maps and hydrological studies in order to determine the potential sites or locations available for the development of a micro-hydropower plant in Tioman Island. The result shows that a total of 10 sites identified to have micro-hydro potential from 26 investigated sites. From the monthly estimated river flow, it can be seen that the hydropower in Tioman Island varies seasonally, having the highest potential during the northeast monsoon season. © 2014 IEEE.